ANALISIS FAKTOR RISIKO STUNTING PADA ANAK BALITA DI DESA WAGIR KIDUL, PULUNG, PONOROGO - Metti Verawati; Latifah Hanum; Lina Ema Purwanti; Anni Fithriyatul Mas’udah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Stunting is a condition where a child's height is shorter than the height of other children his age. Stunting can interfere with brain development, intelligence, physical growth disorders, and metabolic disorders in the body and even cause other dangerous diseases such as cancer and stroke.Methods: The purpose of this study was to determine the dominant factor influencing the incidence of stunting in the working area of the UPT Puskesmas Pulung, Ponorogo Methods: This study is an observational study with a cross-sectional study design and quantitative analysis. This study has a sample of 32 people. The instrument used in this study was a questionnaire. Data analysis using Logistic Linear Regression.Results: The results showed that history of infectious diseases, environmental sanitation, economic factors, mother's knowledge, and parenting patterns significantly affected the stunting status of toddlers with a p-value less than (0.05).Conclusion: Based on the results of this study, it is expected that health workers will provide health education related to stunting, prevention methods through fulfilling nutrition, good sanitation, and preventing infection in children